Penglibatan Golongan Belia dan Cadangan dalam Mengurangkan Kegiatan Mat Rempit - Muhd Khairul Najmi bin Nasir; Athirah Azhar (Trends in Undergraduate Research, 2024)
One of the reasons of societal issues among young people nowadays might be attributed to ‘Mat Rempit's’ or ‘merempit's’ actions. The three objectives of the study are to determine the causes teens involved in Mat Rempit activities, to identify the effects to the teens, and to suggest steps may be taken to prevent Mat Rempit activities among teenagers. This study employs a qualitative methodology by interviewing five respondents. The sample of respondents was chosen randomly. Thematic analysis was used to analyse the data. From the findings peer pressure, social media, money, and self-interest in the automotive industry are the main reasons why teens involved in Mat Rempit activities. These have caused accidents, caught up in more serious societal issues, and excessive financial squandering. It is suggested that to increase the age limits for licence applications, adding more public circuits, and police operations on weeknights. In conclusion, it is hope that the study's findings on the world of motoring would help to inform the public and raise youngsters' knowledge of the risks associated with Mat Rempit activities.